Current issues in cardiovascular therapy - Elliott, Henry L. (Martin Dunitz, 1997)
A succinct text describing various cardio-vascular therapeutic measures which will be of great use to cardiologists wishing to evaluate the latest clinical trials and meta-analyses when managing patients.